The Development of Dairy Farming Inclusion Its Economics Transformation Local Production for Supporting Sustainable Development in Regional Boyolali - Fathimah Tsabitah Al-Khairiyah; Surya Bagus Mahardika; Muhammad Abiyyu Al-Hammam (Jurnal Inovasi Daerah, 2026)
This research aims to analyze economic and environmental impact from dairy farm inclusion in Regional Boyolali. The research used method qualitative with resources type field analyze with random sampling responden dairy farm in Boyolali. This results case study to showed that the role Villagers Units Cooperative (KUD) in sub district Musuk smooth comprehensive and passive activities to membership (dairy farm), the product from dairy farm not purpose of outcome or output and the government policy focus on economic and environmental impact failed with priorities program is food discovery economic with empowerment local dairy farm practice. Therefore, this suggestion for future, government and stakeholder needs synergic, KUD dairy farm and the output dairy farm product (to guide entrepreneur and citizen) but also creating sustainable development goals with economic transformation focus successfully and economics value chain best practice.